PENINGKATAN PENGETAHUAN GURU TENTANG P3K MELALUI PROMOSI KESEHATAN DI SMK KAL 1 SURABAYA - Rinarto, Nisha Dharmayanti; Priyantini, Dwi; Fitriastuti, Annisa Nurayu (UNUSA Press, 2019)
Health promotion is an effort planned to influence other people, whether individuals, groups or communities, so that they do what is expected by health promotion actors. Health promotion of P3K in schools has an effect on the level of knowledge that teachers have about P3K on emergencies. This study aims to see the effect of health promotion on increasing teacher knowledge about first aid at Surabaya KAL-1 Vocational School. Sampling technique with Simple Random Sampling, a total sample of 39 respondents. The research method is Pre Experimental with the One Group Pretest-Posttest approach. Data collection using questionnaires. Data analysis techniques using the Wilcoxon Signed Rank Test. The results of the study showed that the teacher's knowledge before being given a health promotion with an average value of 1.38 and after being given a health promotion obtained an average value of 2.54. The results of statistical tests obtained the results of Asymp. Sig 0.001> α 0.05, which means that there are significant differences. Further analysis found that there was an effect of health promotion on the level of teacher knowledge, so it was hoped that the school would propose to the relevant UPTD for the provision of first aid training in schools